On the Panel with the Risen Christ Adored by Brothers of the Confraternity of the Disciplinants from the Collection of Nizhny Novgorod State Art Museum and Its Author - Guerzi, Chiara (Actual Problems of Theory and History of Art, 2023)
This work is discussed in the context of the artwork of the painter Michele di Iacopo Dai Carri from Ferrara, the presumed author of a corpus of works grouped under the name of the so-called Maestro G.Z. The work from the Russian museum, which entered the artist’s catalogue because of the undeniable stylistic relationship with the other works, is now the only surely dated painting of the group, and therefore, the only chronological reference which allows to establish the sequence of the works by the painter.The article, besides demonstrating the significance of the Nizhny Novgorod panel and confirming its attribution to the Master G.Z. identified with Dai Carri, clarifies the provenance of the work, analizes iconography of the depictions on the both sides of the panel, sheds light on its function as a processional standard of a disciplinants confraternity, and considers the painting in the artistic context of the Ferrara and Bologna during the reign of Nicolò III d’Este (1393–1441) and within the new artistic trends expressed by Alberto da Campione and Jacopo della Quercia, and those, originated by the presence of Gentile da Fabriano in Venice.
Keywords: Confraternity; Disciplinants; panel painting; Emilia confraternities; Ferrarese painting; Schekin collection; Nicolò III d’Este age; late Gothic age